Genesis and evolution of corporate social responsibility - Baltabayeva, A.К. (BUKETOV BUSINESS REVIEW, 2018)
The article examines the genesis of corporate social responsibility (CSR). Various interpretations of CSR, approaches and interpretations of CSR by foreign and domestic authors, and international organizations have also been studied. The basic stages of the evolution of relevant concepts that reflect the essence of CSR as a managerial theory and practice of market behavior of modern business are analyzed. In the article, was discussed the communication of the main concepts associated with CSR: the concept of social responsibility of business, corporate responsibility, the concept of stakeholders (stakeholder theory), social investments, corporate citizenship, social susceptibility, corporate sustainability, corporate social activity, corporate social conscientiousness. The author identified the main differences and features between CSR and alternative concepts, the continuity of their content and the goal orientation are revealed. In the paper the essential content of CSR is described as a multidimensional and multilevel category organically related to the institutional environment of the functioning of corporations. As a result, the conclusion is made about the impossibility of interchangeability of such concepts of CSR and «sustainable development», «corporate citizenship», «corporate social conscientiousness», at the same time the synonymity of CSR concepts and «social responsibility of business» is grounded.